PENYULUHANPENANAMANSAYURAN DENGAN MEDIAPOLYBAG - Suprianto Pasir (UII, 2014)
In the world of agriculture and farming we often hear the term poly bag as agrowing medium, especially in planting to save farmland. Polybag election as a containerplant for cultivation is influenced by several factors such as cheap price, rustproof,durable, lightweight form uniform, not dirty quickly and easily obtained at the farmsupply store or store plastic. Polybag excellent addition to drainage, aeration, so theplants can flourish as dilahan. Determining the size of the poly bag suitable for plantgrowth is expected to improve productivity and efficiency in the use of media andnutrients.